Exploiting the plasticity of primary and secondary response mechanisms in artificial immune systems - Greensmith, Julie; Jackson, Andrew M.; Spendlove, Ian (2016)
One of the key properties of the human immune system is to detect the presence of pathogens, and as such there are numberous immune algorithm which perform anomaly detection and pattern recognition. An additional facet of the human immune system is that an appropriate effector response is generated upon the detection of a pathogen - a process termed the primary response. Additionally the human immune system has the ability to remember the appropriate response to a particular pathogen - the secondary response. The complex orchestration of both the primary and secondary responses are highly dynamic - described in immunological terms as plastic. In this paper we present an overview of the the exact mechanisms of the generation of a T-helper cell primary response and the mechanisms by which it instructs secondary responses and discuss how this can be computationally useful in artificial immune system development.